Application of bioenergetics modelling to fish growth in ponds - Garcés B., Humberto A. (1993)
Applications of bioenergetics modelling to aquacultural systems demonstrate great potential of this technique for solving management problems (Schuur 1991). Bioenergetics modelling has been applied to wild populations of coho and chinook salmon, brown and lake trout, cod, haddock, largemouth bass, yellow perch, walleye, and skipjack and yellowfin tunas, and to a few cultured species like rainbow trout, channel catfish, and gilthead seabream. Mechanistic growth models potentially applicable to red drum have been developed by Kitchell et al. (1978) for tunas and by Cuenco (1982) for channel catfish. Doerzbacher et al. (1988) developed a temperature-compensated von Bertalanffy model to describe growth of tagged drums in Texas bays. However, there seems to be very little published information available for parameterizing a mechanistic growth model for red drum in aquacultural pond systems. Here I present the applications of a bioenergetics-based model developed 10 simulate growth of red drum cultured in Panama.